Autogenous Great Saphenous Vein Graft Bypass versus Stenting in Cath Lab in treatment of Long Segment Superficial Femoral Artery Occlusion- Our Experience in Bangladesh (University Heart Journal, 2025)
Background: Long-segment superficial femoral artery (SFA) occlusion poses significant challenges in peripheral arterial disease management. While Autogenous great saphenous vein (GSV) bypass grafting remains the gold standard, endovascular stenting has emerged as a less invasive alternative. This study compares the outcomes of these two approaches in a Bangladeshi cohort.Objective: To evaluate the efficacy of GSV graft bypass versus catheterization laboratory (cathlab) stenting for long-segment SFA occlusion.Methods: This prospective comparative study was conducted at Bangladesh Medical University (Ex BSMMU), Shahbag, Dhaka and IBN SINA Specialized Hospital, Dhanmondi, Dhaka from January 2022 to July 2024. Thirty patients with long-segment SFA occlusion (>15 cm) were enrolled via purposive sampling and randomly allocated to either GSV bypass (n=15) or stenting (n=15) groups. Primary endpoints included procedural success, patency rates at 6 and 12 months, and complication rates. Secondary endpoints comprised anklebrachial index (ABI) improvement and quality-of-life measures. Data were analyzed using SPSS version 23.0, with statistical significance set at p